Additional file 1 of “Limiting access to iron decreases infection of Atlantic salmon SHK-1 cells with bacterium Piscirickettsia salmonis” - Rodrigo Díaz (10101439); José Troncoso (10642592); Eva Jakob (9572168); Stanko Skugor (10642595) (2021)
Additional file 1: Supplementary file 1 A-M. The evaluation of cytopathic effects in SHK-1 cells infected with P. salmonis. Separate images of cell cultures under four experimental conditions at days 4, 7 and 11 (dpi): non-infected SHK-1 not treated with DFO (SHK-1), non-infected SHK-1 cells treated with DFO (SHK-1 + DFO), infected SHK-1 cells not treated with DFO (SHK-1 + P. sal) and SHK-1 cells infected with P. salmonis and treated with DFO (SHK-1 + P. sal + DFO). Images were taken with the EVOS® FL Color Imaging System (Invitrogen, Thermo Fisher Scientific Inc., Carlsbad, CA, USA) using 10X objective after 3 PBS-1X washes. The scale bar was added by using the image analysis ImageJ 1.37 software (National Institutes of Health, Bethesda, MD, USA). Scale bar = 260 μM.